Matrix Extension Study: Validation of the Compact Dry EC Method for Enumeration of Escherichia coli and non-E. coli Coliform Bacteria in Selected Foods. (27th November 2019) - Mizuochi, Shingo; Nelson, Maria; Baylis, Chris; Green, Becky; Jewell, Keith; Monadjemi, Farinaz; Chen, Yi; Salfinger, Yvonne; Fernandez, Maria Cristina
Abstract: The Compact Dry "Nissui" EC method, originally certified by the AOAC Research Institute Performance Test Method SM program for enumeration of Escherichia coli and non- E. coli coliforms in raw meat products ( Performance Tested Method SM 110402), has undergone an evaluation to extend the method's claim to cooked chicken, prewashed bagged shredded iceberg lettuce, frozen cod filets, instant nonfat dry milk powder, and pasteurized milk (2% fat). Compact Dry EC is a ready-to-use dry media sheet containing a cold-soluble gelling agent, selective agents, and a chromogenic medium, which are rehydrated by adding 1 mL diluted sample. E. coli form blue/blue-purple colonies, whereas other coliform bacteria form red/pink colonies. Users can obtain an E. coli count (blue/blue-purple colonies only) and a total coliform count (red/pink plus blue/blue-purple colonies) after 24 ± 2 h of incubation at 37 ± 1°C. The matrix extension study was organized by Campden BRI (formerly Campden and Chorleywood Food Research Association Technology, Ltd), Chipping Campden, United Kingdom. Method comparison data for cooked chicken, prewashed bagged shredded iceberg lettuce, frozen cod filets, and instant nonfat dry milk powder were collected in a single-laboratory evaluation by Campden BRI. A multilaboratory study was conducted on pasteurized milk (2% fat), with 13 laboratories participating. The Compact Dry EC method was compared to ISO 16649-2:2001 "Microbiology of food and animal feeding stuffs–Horizontal method for the enumeration of beta-glucuronidase-positive Escherichia coli —Part 2: Colony-count technique at 44 degrees C using 5-bromo-4-chloro-3-indolyl beta-D-glucuronide" and to ISO 4832:2006 "Microbiology of food and animal feeding stuffs—Horizontal method for the enumeration of coliforms—Colony-count technique, " the current standards at the time of this study. Each matrix was evaluated separately for E. coli and non- E. coli coliforms at each contamination level (including an uncontaminated level). In the single-laboratory evaluation (cooked chicken, prewashed bagged shredded iceberg lettuce, frozen cod filets, and instant nonfat dry milk powder), colony counts were logarithmically transformed, and then the data were analyzed at each level for sr, RSDr, and mean difference between methods with 95% confidence intervals (CIs). A CI outside a range of −0.5 to 0.5 on the log10 mean difference between methods was used as the criterion to establish a significant statistical difference. In the multilaboratory study on pasteurized milk, after logarithmic transformation, the data were analyzed for sR and RSDR in addition to sr, RSDr, and mean difference with 95% CIs. Regression analysis was performed on all matrixes and reported as r 2 . In the single-laboratory evaluation, statistical differences were indicated between the Compact Dry EC and ISO 16649-2 methods for the enumeration of E. coli in two of five contamination levels tested for lettuce, and in the low contamination level for cooked chicken. For the cooked chicken and lettuce at the low level, only a few colonies were recovered for each method, and thus not a true indication of the methods' performance. For the high contamination level of lettuce, counts varied within the sets of five replicates more than 10-fold for each method, which may have contributed to the significant difference. Statistical differences were also indicated between the Compact Dry EC and ISO 4832 methods for the enumeration of coliforms in two of five contamination levels tested for lettuce, two of five contamination levels of milk powder, and in the low contamination level for frozen fish. For the lowest levels of frozen fish and milk powder, only a few colonies were recovered for each method. For the lettuce and the other level of milk powder, counts varied within the sets of five replicates more than 10-fold for each method, which may have contributed to the significant differences indicated in the those contamination levels. In most cases, mean differences between the Compact Dry EC and International Organization of Standardization (ISO) methods were well below 0.5 log10, and the CIs were within the acceptance criterion (−0.5 to 0.5). The sr and RSDr values were similar for both methods, and r 2 values were >0.92 for all comparisons. In the multilaboratory study, no statistical differences were indicated between the methods. The sr, RSDr, sR, and RSDr values were similar for each method and even slightly smaller in most cases for the Compact Dry EC. The r 2 value was 0.97 in comparison to ISO 16649-2, and 0.99 in comparison to ISO 4832. The Compact Dry EC offers comparable results to the ISO standard plating methods in a space saving, easy-to-use format.